Dampak Pemasaran Digital bagi UMKM Pondok Etam - Satriadi Satriadi; Cecilia Yeo; Fitri Handayani; Ratna Sari; Wulandari Wulandari (Universitas Kristen Indonesia Toraja, 2022)
Micro, Small and Medium Enterprises or MSMEs are businesses formed by a group of people or individuals independently. Digital marketing is a strategy or marketing activity such as product promotion carried out through digital media. Marketing strategies through digital marketing are needed so that MSMEs can compete and reach more consumers. Pondok Etam is an MSME engaged in the culinary field that sells various kinds of food products that are focused on the target market for teenagers to adults. The purpose of this study is to determine the impact of digital marketing for MSME Pondok Etam. The research method used is a qualitative descriptive method. Data collection techniques were carried out by in-depth interviews. The result of this study is that digital marketing has a positive impact on the MSME of Pondok Etam, because there is an increase in brand awareness and a significant increase in sales